Pyrolysis of rice straw; Effect of reaction parameter on the product yields and compositions - Razi, Ahmad; Khairuddin, Md Isa; Khairul Nizar, Ismail; Khudzir, Ismail (Universiti Malaysia Pahang (UMP), 2011)
Regional Conference in Environmental and Earth Resources 2009 (RCER 2009) organized by Universiti Malaysia Pahang, from 7th - 8th December 2009 at MS Garden, Kuantan, Pahang, Malaysia.